Assessment in homeschooling: Emerging topics - Emilia Restiglian; Serena Busato (Ricerche di Pedagogia e Didattica, 2025)
The spread of homeschooling practices in many countries responds to the need of many families to find an alternative to traditional school offerings that respect the well-being, potential and learning times of the child. Assessment, a fundamental element of educational planning in conventional schools, is not considered equally in homeschooling settings, despite its formative value and the possibility that it can act as an element capable of restoring centrality to the child. With references to international literature, the contribution reports an exploratory research conducted in the Italian context that sought to delve into the topic of the methods of examining homeschooling students and the perceptions of school personnel involved in their assessment process. The triangulation of data from different studies on the same topic and from various perspectives (families, teachers and headteachers) helped grasp the phenomenon’s complexity and the possibility of defining a school that works for all its students.